Local Wisdom in Income Accounting: The Case of Karawo Entrepreneurs - Mohamad Anwar Thalib; Nurjayanti Langgai; Mohamad Akbar Ali (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2026)
This study is motivated by the tendency to view income accounting only as technical recording, which limits its connection to local wisdom. This issue is important because, in micro-enterprises such as Karawo entrepreneurs in Gorontalo, accounting is strongly linked to cultural and spiritual values. The research questions explore how Karawo entrepreneurs practice income accounting and how local values are reflected in it. The novelty lies in formulating revenue accounting practices based on local culture through a spiritual paradigm and an Islamic ethnomethodology approach. A qualitative method was applied with five stages of analysis: charity, knowledge, faith, revealed information, and courtesy. Data were collected through observation and interviews. The findings identify four practices: recording in memory, flexible management, daily estimation, and simple paper notes. These are infused with non-material values, especially gratitude, reflected in the cultural wisdom lumadu Diila o’onto, bo wolu-woluwo (unseen but present). The study concludes that micro-accounting is not merely economic recording but an expression of cultural and spiritual values. Theoretically, it expands the concept of income accounting. Practically, it provides a foundation for developing local wisdom-based accounting models to empower MSMEs. Furthermore, this study implies that policymakers and practitioners should integrate local cultural and spiritual values into financial literacy programs and MSME development strategies. By doing so, accounting practices can become more contextual, inclusive, and acceptable to local communities. For academics, this research encourages the development of alternative accounting paradigms that are not solely based on Western rationality but also incorporate indigenous knowledge systems. These implications support the sustainability and resilience of MSMEs by aligning formal accounting practices with deeply rooted cultural values.